Structural basis for different specificities of acyltransferases associated with the human cytosolic and mitochondrial fatty acid synthases. - Bunkoczi, G; Misquitta, S; Wu, X; Lee, W; Rojkova, A; Kochan, G; Kavanagh, K; Oppermann, U; Smith, S (2009)
Animals employ two systems for the de novo biosynthesis of fatty acids: a megasynthase complex in the cytosol (type I) that produces mainly palmitate, and an ensemble of freestanding enzymes in the mitochondria (type II) that produces mainly octanoyl moieties. The acyltransferases responsible for initiation of fatty acid biosynthesis in the two compartments are distinguished by their different substrate specificities: the type I enzyme transfers both the acetyl primer and the malonyl chain extender, whereas the type II enzyme is responsible for translocation of only the malonyl substrate. Crystal structures for the type I and II enzymes, supported by in silico substrate docking studies and mutagenesis experiments that alter their respective specificities, reveal that, although the two enzymes adopt a similar overall fold, subtle differences at their catalytic centers account for their different specificities.